Diffuse idiopathic skeletal hyperostosis presenting as spinal cord compression combined with intervertebral space narrowing: A case report - Zhang Jiaqi; Xu Lichen; Xia Dongxue; Tang Wei; Wang Wei (Journal of International Medical Research)
This report highlights an unusual case of a woman in her 70s who presented with diffuse idiopathic skeletal hyperostosis and an initial symptom of spinal cord compression and associated spinal degeneration. She presented with progressive thoracolumbar pain, bilateral lower limb weakness, and sensory deficits. Imaging showed continuous osteophytes in the anterior and lateral spine, multiple levels of intervertebral space narrowing, marked ligament ossification at T10/11, and severe spinal stenosis. Diffuse idiopathic skeletal hyperostosis was diagnosed and spinal cord compression was significantly reduced after laminectomy. Although diffuse idiopathic skeletal hyperostosis is relatively common in elderly patients, cases of spinal cord compression are still rare, and the combination of intervertebral space stenosis, and ossification of the ligamentum flavum may be misdiagnosed as degenerative spondylopathy. This case suggests the possibility of intervertebral stenosis and ossification of the thoracic ligamentum flavum coexisting with diffuse idiopathic skeletal hyperostosis, highlighting the importance of diagnostic imaging in the early stage of patient management.